모바일 엣지 컴퓨팅 환경에서 종속 태스크를 위한 다중 목적 계산 오프로딩 알고리즘 - 구설원(Seolwon Koo); 임유진(Yujin Lim) (정보과학회 컴퓨팅의 실제 논문지, 2021)
계산 오프로딩은 한정적인 배터리 수명과 계산 능력을 갖추고 있는 디바이스가 많은 양의 데이터와 계산 요구를 만족시키기 위한 기술이다. 하지만 지연시간에 민감한 응용사례인 VR/AR과 스마트 팩토리와 같은 도메인에는 서비스 품질을 보장할 수 없어, 이를 위해 최근 모바일 엣지 컴퓨팅에 관한 연구가 많이 진행되고 있다. 본 논문에서는 스마트 팩토리와 같이 태스크들 사이에서 종속성이 존재하는 환경을 고려하였다. 이러한 환경에서 PSO(Particle Swarm Optimization) 기법을 사용하여 종속적인 태스크들의 오프로딩 여부를 결정하는 다중 목적 최적화 알고리즘을 제안한다. 본 제안 기법의 목적은 태스크 지연시간을 만족시키면서도 서비스의 에너지 소모량과 시스템 비용을 최소화하는 것이다. Computation offloading is a technology for satisfying large amounts of data and computing requirements for devices with limited battery life and computation capability. However, it is difficult to satisfy the QoS (quality of service) for domains such as VR/AR and smart factory, which are latency-sensitive applications. To solve this problem, mobile edge computing (MEC) has recently been widely considered. In this paper, we assumed application environments in which a dependency existed among the tasks, such as in a smart factory. We proposed a multi-objective optimization algorithm using PSO (particle swarm optimization) for offloading decisions in the MEC environment. The algorithm was proposed to optimize system costs and energy consumption within conditions of limited latency. KCI Citation Count: 0